Penegakan Hukum Terhadap Tindak Pidana Pencurian Hasil Hutan Bukan Kayu (Getah Pinus) di Kabupaten Tana Toraja - Tandilese, Duwisno Ipang; Muchtar, Syamsuddin; Mirzana, Hijrah Adhyanti (Al-Mizan (e-Journal), 2024)
This study aims to analyze law enforcement against theft of non-timber forest products (pine resin) in Tana Toraja and inhibiting factors in law enforcement. This research is normative-empirical research using a statutory approach, conceptual approach, and sociological enforcement with data sources in the form of observations, documentation, and interviews with the police, prosecutors, and judges who handle the case. The results of this study indicate that law enforcement against the crime of theft of forest products in Tana Toraja Regency substantially uses Law Number 41 of 1999 concerning Forestry, but structurally, law enforcers are still less effective in handling it. While the inhibiting factors affecting law enforcement, namely structurally, the police are still less effective in acting according to the mandate of the law, there are still unscrupulous officials who intervene in the taking of pine resin; and related facilities or facilities are not adequate in supporting the implementation of law enforcement against the crime of pine resin theft.